SYSTEMATIC LITERATURE REVIEW OF JOB SATISFACTION: AN OVERVIEW AND BIBLIOMETRIC ANALYSIS - Oktaviani, Rosana; Sopiah (Transpublika Publisher, 2022)
Job satisfaction is the main variable that must be considered in managing human resource practices. Job satisfaction discusses the extent to which employees are satisfied or dissatisfied with their jobs are caused by several factors that motivate them. This study aims to dig deeper into job satisfaction variable. In achieving this goal, the researchers used a systematic review using PRISMA method and bibliometric analysis techniques which took journals from Science Direct and Emerald during 2017-2022. The results of the screening on the PRISMA method produced 30 (thirty) articles written by 95 (ninety five) authors. Based on the 30 (thirty) articles collected, the results of this study found that there are 4 (four) categories that explain several variables that related to job satisfaction, including leadership, salary, organizational commitment, and job stress. Overall, the research is expected to be the right reference for further research, especially researchers who will examine titles that related to job satisfaction.